2021
DOI: 10.1111/1462-2920.15684
|View full text |Cite
|
Sign up to set email alerts
|

Household environmental microbiota influences early‐life eczema development

Abstract: SummaryExposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The second unexpected finding of our research was that neither urine cotinine concentration nor parental smoking were predictors of asthma or any of the other studied diseases. In other studies [27,29], parental smoking and cotinine levels were strong predictors of asthma development. Nevertheless, just 31% of investigated families reported exposure to tobacco smoke.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The second unexpected finding of our research was that neither urine cotinine concentration nor parental smoking were predictors of asthma or any of the other studied diseases. In other studies [27,29], parental smoking and cotinine levels were strong predictors of asthma development. Nevertheless, just 31% of investigated families reported exposure to tobacco smoke.…”
Section: Discussionmentioning
confidence: 69%
“…Research by O'Connor et al [27] based on children up to 7 years of age showed that higher concentrations of cockroach, mouse, and cat allergens in house dust in the first three years of life were associated with a lower risk of asthma (for cockroach allergen, the odds ratio for an increase in the interquartile range 0.55; 95% CI, 0.36 to 0.86; p < 0.01). At the same time, the abundance of a number of bacterial taxa in house dust was associated with increased or decreased asthma risk [29]. On the other hand, it is known that diesel pollution and exhaust fumes intensify the action of allergens, which may affect the development of allergic inflammation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, early-life environmental microbial exposure is critical to immune development and may modulate allergy risk. 61,62 Of note, this meta-analysis highlighted the importance of in utero programming in allergy development.…”
Section: Discussionmentioning
confidence: 85%
“…The environmental pathogenic mechanisms of eczema in children may be multifaceted and have not been fully understood, which may be related to the dysregulation of cytokines and inflammatory mediators directly or indirectly induced by chronic exposure to xenobiotics ( 50 52 ). Besides, evidence have proved that indoor exposure to exogenous microbiota may alter intestinal microbiota in children, and thus regulate the immunological functions ( 53 55 ). In addition, indoor wood materials and coating on the walls may release organic pollutants such as organophosphates or brominated flame retardants, which may also exert hazardous effects on gut microbiota and potentially impair immune systems ( 56 , 57 ).…”
Section: Resultsmentioning
confidence: 99%